STRATEGI KABUPATEN SUMBAWA MENYIAPKAN SUMBER DAYA MANUSIA BERKUALITAS GUNA MENGHADAPI REVOLUSI INDUSTRI 4.0 - Minten Ayu Larassati; Muammar Khadafie; Apriadi Apriadi (Jurnal Pendidikan Ilmu Sosial, 2021)
The district government needs human research development to have quality and face industrial era 4.0. This is urgent, due to human resource development staff plays active role and dominant in every organizational activity. This research aims at identifying process and human research development strategies which has quality in facing industrial era 4.0. This qualitative descriptive research use documentation, interviews, and observation as collecting data method. Here are some strategies to achieve quality human resource development in order to be success in term of faster, easy, and efficient. Mastering technology, make digital innovation such as services system in application forms, planning policy for 2021. The process of establishing human resources is changing life patterns in line with industrial era 4.0. It is practicing education by guidance booklet need analysis. It is a planning roadmap for 2021. It is a practicing guidance booklet in line with the need of the industrial era of 4.0. the strategy and process of human resource development enhancement could be done maximally by the new year. It is when the vision and mission of government will be changed following 4.0 industrial era.